A Multilevel Analysis to Determine the Factors Associated with Institutional Delivery in Nepal: Further Analysis of Nepal Demographic and Health Survey 2016 - Bidusha Neupane; Sujan Rijal; Srijana GC; Til Bahadur Basnet (SAGE Publishing, 2021)
Background: One out of two neonatal deaths and 2 out of 5 maternal deaths occur at home in Nepal. An essential intervention in reducing maternal mortality and neonatal death is institutional delivery. The objective of this study was to find out the external environmental, predisposing, and enabling factors associated with the use of institutional delivery care in Nepal. Methods: Data from Nepal Demographic and Health Surveys (NDHS) 2016 was used to estimate socio-economic, provincial, and use of media differentials with institutional delivery under the Andersen behavioral model framework using multilevel regression analysis. Results: More than half of the women (60.9%) among 3899 women with last birth had their babies delivered in a health facility. In the multilevel logistic regression analysis, we found that women from province 2 (OR = 0.47 95%CI: 0.28-0.79) were significantly less likely to deliver in health institutions, and province 7 (OR = 1.76, 95%CI: 1.05-2.94) were significantly more likely deliver in a health institution. Age (OR = 0.94, 95%CI: 0.92-0.95) was also significantly associated with the place of delivery. Women with higher education (OR = 3.17, 95%CI: 2.09-4.81) were most likely to go for institutional delivery. The odds of women opting for institutional delivery were 3 folds more for those who had visited Antenatal Care (ANC) 4 or more times compared to those who did not. Conclusion: The results highlight the need for governments and health care providers to emphasize the promotion of institutional delivery and ANC visits as per protocol with a special focus on underprivileged communities. The use of multi-media is a vital strategy to promote the use of institutional delivery services.